MAKNA NORMATIF TAGAN DALAM WALIMAH URUSY MASYARAKAT PARIT BARU SELAKAU KABUPATEN SAMBAS - Lestari, Ika Ayuni; Wagiyem, Wagiyem; Wibowo, Arif (Al-Usroh, 2023)
Objectives of this study: 1) To know more clearly the Tagan practice system at the walimah urusy of the community from Selakau District of Sambas Regency in Parit Baru Village. 2) Legal firmness sourcedfrom the Qur’an, hadith, ijma', or qiyas as well as local personalities of ulama who explain the Tagan tradition in terms of the principle of dain (debt) or similar as a syara' argument. This study uses a qualitative method with the type of empirical-normative research. The techniques for collecting data are library research, interviews, observations, and documentation with primary data sources from the expert and secondary data sources from literacy references. The technique to validate the data is a reliability test with a research site in Parit Baru Village, Selakau District, Sambas Regency. The results of the study: 1) There is a tradition in Barit Baru village called Tagan, and the practice of Tagan was held by the wedding ceremony, the community donates goods, food ingredients, food, drinks, tents, sound music, etc. to the practice organizers as much as they can from the donation, where this donation must be exchanged Later with the same item while the donors are holding the wedding. 2) Tagan traditions based on the dain principle must be paid exactly as they are due, without reducing the level, price, amount and taste. However, with the times that are increasingly advancing and changing, there will of course be significant changes in the quality of the merchandise. So the Tagan should be paid at the fair price of the goods at that time and not following the previous price. The rule of Tagan crowns is permissible and does not contain the elements of usury. The law of Tagan is permissible and does not contain the elements of usury. So linearly, walimatul 'ursy which uses the Tagan tradition is halal.